Fibroelastoma in an unusual location: a rare cause of multiple cerebrovascular events - Mary Mashicharan; Zein El-Dean; Viktor Zlocha; Jeffrey Khoo DPhil (Echo Research and Practice, 2019)
Fibroelastomas are rare, primary cardiac tumours with a predilection for valvular endothelium and a propensity to embolise. We present the case of a 72-year-old male with multiple cerebrovascular events (CVA) despite oral anticoagulation. Transoesophageal echocardiography (TOE) revealed a small highly mobile left atrial mass with frond-like projections attached by a stalk to the orifice of the LAA. The mass was surgically excised and confirmed to be a fibroelastoma on histological examination. This case report describes a rare but treatable source of multiple cerebrovascular events and highlights the utility of TOE in the assessment of cardiac embolic source.